Językowo-kulturowy obraz męskości w felietonach Tomasza Raczka - Magdalena Majewska (Ksiegarnia Akademicka Publishing, 2019)
The Linguistic and Cultural Image of Masculinity in Tomasz Raczek’s Feuilletons In this paper, the author presents the linguistic layer of Tomasz Raczek’s feuilletons published in the “Wprost” weekly. Analysed are the various linguistic means, phraseologisms, and lexemes occurring in Raczek’s texts, which showcase masculine and non-masculine social attitudes, and thereby the subjective value system represented by the author of the “Ekran osobisty” (‘Personal screen’) series of feuilletons. Moreover, the paper presents the narrative strategies of Raczek’s feuilletons, revealing the linguistic and cultural image of masculinity in Raczek’s texts: the culture of intertextuality and conceptual metaphors.